Predicting Silica Deposition from Superheated, Pressurized Steam Using Numerical Modeling of Nucleation, Agglomeration and Deposition - Silje Bordvik; Titus S. van Erp; Seniz Ucar; Erling Næss (Energies, 2023)
A model that can be used to quantify silica deposition from superheated depressurized steam is developed. Classical nucleation theory, agglomeration and deposition onto a wall are combined in a numerical model that calculates the concentration profile, the particle size distribution and the deposition in a flow through a pipeline after a sudden increase in supersaturation. The work presented here is an important step in understanding the mechanisms governing precipitation from supercritical and superheated steam as produced by deep geothermal wells drilled in magmatic areas. The power potential in such systems can be significantly higher than for conventional systems if utilized efficiently. The presented results can be applied to improve industrial designs and decrease energy costs. The model predicts the amount of precipitation along a pipe at various supersaturations, and the resulting deposition velocity in a straight pipe correlates fairly well with recent experimental results. There is a high number of nanocolloids formed close to the pressure reduction position, where deposition is at its maximum. Downstream, larger agglomerates develop, and deposition decreases as the number of particles and the overall concentration decreases. The local maximum deposition rate increases with increasing supersaturation. The calculations show that deposition mechanisms are as important as the chemical process of solidification when estimating where and how most material will be deposited. The rapid formation and deposition of solids predicted indicate that depressurization along with solid capture could be used to rid fluid of silica.